2011
DOI: 10.1007/s00439-011-1077-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression signature of epidermolysis bullosa simplex

Abstract: Epidermolysis bullosa simplex (EBS) is a skin disorder resulting from a weakened cytoskeleton of the proliferative compartment of the epidermis, leading to cell fragility and blistering. Although many mutations have been identified in intermediate filament keratins KRT5 and KRT14, detailed pathogenic mechanisms and the way these mutations affect cell metabolism are unclear. Therefore, we performed genomic and transcriptomic study in six Canadian EBS patients and six healthy subjects. We first characterized the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 78 publications
(35 reference statements)
0
17
0
Order By: Relevance
“…4E). Furthermore, only 11 upregulated genes at E18.5 and 18 genes at P0 in Krt1 2/2 skin were common to human EBS patient skin (Bchetnia et al, 2012). Based on these data we conclude that the gene expression signature from Krt1 2/2 mice shows more similarities to human inflammatory skin diseases than to keratin-associated defects in mice and humans (supplementary material Table S3).…”
Section: Krt1 Links Barrier Function To Inflammation and Innate Immunitymentioning
confidence: 72%
See 1 more Smart Citation
“…4E). Furthermore, only 11 upregulated genes at E18.5 and 18 genes at P0 in Krt1 2/2 skin were common to human EBS patient skin (Bchetnia et al, 2012). Based on these data we conclude that the gene expression signature from Krt1 2/2 mice shows more similarities to human inflammatory skin diseases than to keratin-associated defects in mice and humans (supplementary material Table S3).…”
Section: Krt1 Links Barrier Function To Inflammation and Innate Immunitymentioning
confidence: 72%
“…Transcriptome data from AE (E-GEOD-12511), psoriasis (E-GEOD-13355), Krt5 P0 (E-GEOD-7663) and EBS (E-GEOD-28315) were downloaded from the EBI server for the further comparison analysis (Bchetnia et al, 2012;Gudjonsson et al, 2010;Lu et al, 2007;Sääf et al, 2008). For data processing GNU R (www.rproject.org) with the Bioconductor packages (www.bioconductor.org) were used.…”
Section: Rna Preparationmentioning
confidence: 99%
“…In future studies, investigation of how other types of plectin mutations, such as in EBS Ogna (Walko et al, 2011), and EBS caused by keratin mutations affect nuclear morphology and gene expression will be of great importance. Recent mRNA expression profiling studies, implicating pathways related to interleukins, lipid metabolism and keratinisation, suggest that transcriptional mechanisms might indeed play a role in EBS (Bchetnia et al, 2012;Lu et al, 2007). Ultimately, identifying the impact of altered nuclear mechanics in the pathophysiology of blistering skin diseases could shed new light on our understanding and treatment of these complex and painful conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In epidermolysis bullosa simplex (EBS), the severity of disease frequently correlates with the site of mutation in KRT5 and KRT14, with mutations in the region responsible for linking the small acidic type I keratins ( KRT1, KRT5 ) to the larger neutral-basic type II keratins ( KRT10, KRT14 ) giving rise to more severe phenotypes due to the overall disturbance of the KIF network [2]. A recent study investigating the genomic changes occurring in EB versus normal skin confirmed recurrent mutations in KRT5 / KRT14 and identified EB gene signatures that point to dysfunction in lipid metabolism as well as epidermal keratinization [4]. EB is also characterized by mutations in various cell adhesion genes, including lamin 332, integrins, and collagen VII recently reviewed in [5].…”
Section: Loss Of Tissue Integritymentioning
confidence: 99%